Development of e-LKPD Using Flip PDF Professional on Coordination System Material for F Phase Students - Rachmat Meydi; Afreni Hamidah; Raissa Mataniari (Postgraduate, University of Mataram, 2024)
Coordination system is a complex material due to its many sub-discussions. Teachers’ limited time to discuss questions with students causes students to have difficulties in understanding the material. To overcome this problem, e-LKPD which can streamline learning time and act as a solution to students' difficulties related to the lack of time to do practice questions is required. This research aims to develop an e-LKPD using Flip PDF Professional on coordination system material and analyze the feasibility of the developed product. This research uses the ADDIE development model which consists of Analyze, Design, Develop, Implement and Evaluation. The results of the research show that the e-LKPD developed obtained a percentage of 93.30% in the